Comparative Anthropometric Analysis of Facial Dimensions and Types in Qazvin, Iran and DeraGhazi Khan, Pakistan - Maryam Azizi; Gholamreza Hassanzadeh; Mohammad Barbarestani; Makan Sadr; Ali Dehbashipour; Noushin Alaghbandha; Mohammad Abrar Abbas; Omran Heydar Zeidi (Anatomical Sciences Journal, 2014)
Introduction: Cephalometry is an efficient tool for anthropometric studies. This study sought to assess facial dimensions and types of adults residing in Qazvin (Iran) and Dera Ghazi (DG) Khan (Pakistan). Methods: In this cross-sectional study, a total of 300 ethnic populations of Qazvin and 365 ethnic populations of DG Khan aged between 18-55 years were randomly selected and evaluated. The subjects had no maxillofacial deformities or history of head/facial trauma. Facial height and breadth, nasion-prosthion height, upper facial index, total facial index, facial type and profile were evaluated in subjects. Results: The difference in total facial index between males of Qazvin and DG Khan was statistically significant (P<0.005). This index was significantly different between Qazvin and DG Khan females as well (P<0.005). The mean upper facial index was greater in Qazvin males and females compared to DG Khan and the difference in this respect between males of the two locations was statistically significant (P=0.006). The most and the least common facial types in Qazvin were hyperleptoprosopic and euriprosopic types, respectively whereas, leptoprosopic and mesoprosopic types were the dominant facial types among males and females of DG Khan hypereuryprosopic face was rare in both genders. Orthognathic profile was the dominant facial profile in Qazvin and DG Khan while the least common profile in both locations was prognathic profile. Conclusion: Based on the obtained results, facial index in both genders residing in Qazvin was significantly greater than that those residing in other countries and this may be due to the long facial height and narrow facial breadth in this area.